FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN IUFD DI RSUD ENDE - SULANSI SULANSI; HENDRIKUS MBIRA (JURNAL INFO KESEHATAN, 2013)
Intra-uterine fetal death (IUFD), the death of the fetus in the womb with a gestational age > 22 weeks and fetal weight > 500 grams. In Ende district in 2011 amounted to 102 out of 2,583 live births. Ende in hospitals by 65 of 1,383 live births. Research purposes to determine the factors that influence the incidence of IUFD. Quantitative research, with a case-control design. Population, the incidence of IUFD as the case throughout the entire labor and the baby alive as control. Case 43 samples and 43 control samples. Processing the data with multivariate, bivariate probability 0.05 and odds ratio (OR). The results showed no significant effect between the ANC and IUFD, a significant effect between the diseases that accompany pregnancy IUFD. Very significant disease is hyperthyroidism, hypertension, can lead to IUFD of 7 times. Complications of hypertension could potentially lead to IUFD 7 times and there was no effect of pregnancy on IUFD traumatic. Potentially causing traumatic IUFD by 2 times. In conclusion, there is significant influence between the ANC and the diseases. Suggested to midwives and health centers in order to continue to provide education on the importance of ANC.